Casual and Intimate Style Uttered by Eloise Bridgerton in “Bridgerton 2” TV Series - Sartika Handayani (LPPM Universitas Bumigora Mataram, 2023)
This research focused on finding out the use of casual style and intimate style from Eloise Bridgerton character’s utterances in “Bridgerton 2” TV series. The aim of this research is to get understanding how close and intimate Eloise's relationship is with her family and friends. Joos's (1967) theory of language style was used in this research. And then, the researchers also conducted the speech functions theory from Holmes & Wilson (2017). The researchers employed descriptive qualitative method as the method of the research which is proposed by Creswell & Creswell (2018). For collecting the data, the researchers used the method of observation and the techniques of non-participatory by Sudaryanto (2015). Furthermore, the method of referential identity and the technique of competence in equalizing by Sudaryanto (2015) were used for analyzing the data. As the result, the researchers found out 16 data for language style. The 16 data derived from 7 data of casual style and 9 data of intimate style. Moreover, 17 data for speech functions which derived into 9 data of expressive function, 5 data of directive function, 2 data of referential function, and 1 data of metalinguistic function.